The influence of supply chain sustainability practices on suppliers - Wang, X.; Wood, Lincoln (2016)
Literature shows that focal firms (downstream in supply chain, the customers) which initiate supply chain sustainability (SCSIs) can increase their financial performance; however, the impact of SCSIs on the suppliers (upstream in supply chain, supplying firms) is unclear. This chapter analyzes the costs and benefits from the perspective of suppliers in SCSIs by focal companies. Furthermore, impact of suppliers-specific characteristics (firm size, resources dependence setting and self-sustainability) on SCSIs are investigated. According to the findings, we propose a performance implication-based conceptual model of SCSIs from the perspective of suppliers. We conclude that costs of SCSIs happen immediately to suppliers in implementation, but the benefits are expected in long run. These suppliers-specific characteristics are the decisive factors if suppliers can survive over short-run costs and reach the long-run benefits. This chapter extends the understanding of SCSIs from focal companies to suppliers while providing managerial support on collaboration between supply chain actors.